Spider [videorecording (Blu-Ray)] - McGrath, Patrick, 1950- (Sony Pictures Classics, 2022)
In a London halfway house, a paranoid-schizophrenic struggles to cope with his illness while trying to unravel a mysterious and tormented past, specifically an event from his childhood that occurred after he came to believe that his father was having an affair.